2022
DOI: 10.1111/jfbc.14464
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and enzyme inhibitory properties of sacha inchi ( Plukenetia volubilis ) protein hydrolysate and its peptide fractions

Abstract: The objective of this study was to determine the in vitro activities such as antioxidant and inhibitions of angiotensin converting enzyme, dipeptidyl peptidase‐IV, prolyl oligopeptidase, and 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A reductase of sacha inchi protein hydrolysate (SPH) and its membrane ultrafiltration peptide fractions. SPH was prepared after hydrolysis of sacha inchi protein using papain followed by separation into peptide fractions (F1: <1 kDa, F2: 1–3 kDa, F3: 3–5 kDa, and F4: 5–10 kDa) via ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…At the same time, it was also a component amino acid of the endogenous antioxidant GSH, which played an important role in the antioxidant system of the body. In addition, the classification of amino acids showed that LPH contained a significant number of hydrophobic amino acids (HAAs), which accounted for 27.2% of the total It is reported that peptides’ solubility in lipids may be increased by the presence of HAAs, which could facilitate their entry into target organs and thus increase the antioxidant activity in vitro (Suwanangul et al., 2022). In addition, acidic amino acids and basic amino acids with high content in LPH could play an antioxidant role by chelating metal ions and scavenging free radicals, respectively (Phongthai & Rawdkuen, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it was also a component amino acid of the endogenous antioxidant GSH, which played an important role in the antioxidant system of the body. In addition, the classification of amino acids showed that LPH contained a significant number of hydrophobic amino acids (HAAs), which accounted for 27.2% of the total It is reported that peptides’ solubility in lipids may be increased by the presence of HAAs, which could facilitate their entry into target organs and thus increase the antioxidant activity in vitro (Suwanangul et al., 2022). In addition, acidic amino acids and basic amino acids with high content in LPH could play an antioxidant role by chelating metal ions and scavenging free radicals, respectively (Phongthai & Rawdkuen, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Protein hydrolysates are defined as a complex mixture of peptides and free amino acids produced by enzymatic hydrolysis, which increases the bioavailability of proteins and reduces the immunoreactivity of native proteins 8 . Studies reported that enzymatically hydrolyzed Sacha inchi protein has antioxidant, antihypertensive, enzyme inhibition (α‐amylase, α‐glucosidase and pancreatic lipase) activities 9,10 . Inspired by diabetes‐related enzyme (α‐amylase and α‐glucosidase) inhibitory activities, it is speculated that SIM hydrolysate may also have inhibitory activity on DPP‐IV, which is also an important enzyme related to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies reported that enzymatically hydrolyzed Sacha inchi protein has antioxidant, antihypertensive, enzyme inhibition (⊍-amylase, ⊍-glucosidase and pancreatic lipase) activities. 9,10 Inspired by diabetes-related enzyme (⊍-amylase and ⊍-glucosidase) inhibitory activities, it is speculated that SIM hydrolysate may also have inhibitory activity on DPP-IV, which is also an important enzyme related to diabetes. As expected, in previous studies, 11 we employed proteases to hydrolyze SIM protein, and found that the hydrolysates exhibited DPP-IV inhibition activity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have explored the antioxidant properties of protein hydrolysates or bioactive peptides from plant sources . Enzymes, such as pepsin, papain, and flavorzyme, were used to produce sacha inchi (Plukenetia volubilis L.) protein hydrolysates, of which the pepsin hydrolysate showed the highest hydrolysis degree and antioxidant activity . The alkaline protein hydrolysate of golden melon (Cucurbita pepo L. var.…”
Section: Introductionmentioning
confidence: 99%